Top Incomes in Chile using 50 years of household surveys: 1957 - 2007 - Claudia Sanhueza; Ricardo Mayer (Estudios de Economía, 2011)
Using household surveys that cover more than 50 years of the political and economic history of Chile, we investigate changes in the shape of the distribution of income in Chile, and in the composition of top 10% and top 1% incomes. In line with international evidence, top incomes concentration appears to be countercyclical in the short run. For the entire length of this survey, this concentration shows roughly an inverted U-shape, peaking at the end of the 80s. These changes correspond approximately with different economic policy regimes prevailing in Chile. We observe important changes in the composition of top income groups related to greater relative importance of women, employees and college schooling levels. These changes are stronger for the top 10% than the top 1% of incomes. Additionally, using a national level panel of households for the period 1996-2006 we explore correlations between probabilities of permanence and arrival to the top decile with variables such as composition of the household, ownership of physical and human assets, job quality and changes in the numbers of household members working in the labor market.
Keywords: D31; J6; 330; income distribution; income mobility; Einkommensverteilung; Chile